2021
DOI: 10.1101/2021.01.21.427111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The photosensitive phase acts as a sensitive window for seasonal multisensory neuroplasticity in male and female starlings

Abstract: Traditionally, research unraveling seasonal neuroplasticity in songbirds has focused on the male song control system and testosterone. We longitudinally monitored the song and neuroplasticity in male and female starlings during multiple photoperiods using Diffusion Tensor and Fixel-Based techniques. These exploratory data-driven whole-brain methods resulted in a population-based tractogram uncovering microstructural sexual dimorphisms in the song control system and beyond. Male brains showed microstructural he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 110 publications
1
4
0
Order By: Relevance
“…In general both groups presented similar neuroplasticity changes, both in volume and diffusion parameters, starting during the photosensitive period, as thyroid hormones decline. In line with the prior longitudinal MRI study ( Orije et al, 2021a ), the FA value of several parts of the song motor pathway, anterior forebrain pathway but also visual system and molecular layer of the cerebellum increase gradually over time. Post-hoc linear mixed model analysis revealed subtle interactions over time between the different groups.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…In general both groups presented similar neuroplasticity changes, both in volume and diffusion parameters, starting during the photosensitive period, as thyroid hormones decline. In line with the prior longitudinal MRI study ( Orije et al, 2021a ), the FA value of several parts of the song motor pathway, anterior forebrain pathway but also visual system and molecular layer of the cerebellum increase gradually over time. Post-hoc linear mixed model analysis revealed subtle interactions over time between the different groups.…”
Section: Resultssupporting
confidence: 83%
“…However, starlings have far less PNNs, compared to closed-ended learning zebra finches, suggesting that PNN might play less of a role in the control of seasonal neuroplasticity of open-ended learning starlings ( Cornez et al, 2017 ). Our prior studies suggested myelination rather than PNNs as another candidate mechanism that contributes to ending a sensitive window in open-ended learners like starlings ( Orije et al, 2021a ). In the control group, several tracts including OM, TrO and tFA increased in FA value upon photostimulation, due to decreased radial diffusivity, which implies an increase in myelination ( Song et al, 2002 , 2005 ; De Groof et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations